Main trends solving the problems of degradation and desertification in Ukraine - Movchan, M. (Land Management, Cadastre and Land Monitoring, 2017)
Land resources ofUkraineare characterized by soil cover, which is 60% of the black soil - unique in their structure, properties and potential fertility of soils. They are characterized by deep humusovanyy layer is well defined granular structure, density almost perfect structure, adequate and moderate supply of nutrients. Unfortunately, these model objects are preserved only in virgin conditions. It turned out that the world's best black soil ( "King soils" by V. Dokuchaev) is very sensitive to human interference and under the influence of anthropogenic factors can quickly degrade. One of the main reasons for the deterioration of the quality of the land, especially agricultural land, are: neglect of scientifically based methods of agriculture including crop rotation system failure and technologies for cultivation of crops. So on lands subjected to water erosion stopped work on land management on contour reclamation of the territory. To overcome negative degradation processes that occur Land Resources of Ukraine propnuyetsya apply restrictions in land use, the formation of which provide protection and rational use of land resources, limiting economic activity (which leads to negative changes in the state of land and the development of adverse processes) and sustainable land use. The priority areas to prevent degradation and restore degraded land offered include: the promotion of afforestation and reforestation, especially protective forest strips; creating landscape-adaptive farming systems and reclamation of the contour of the territory in the areas of advanced water erosion; restoration of marshes and wetlands for biodiversity, mitigating climate change and improving water quality. Due to the predominance of agriculture land on lease basis formed important is to establish a process of land use restrictions (encumbrances) in land use.Keywords: land degradation, desertification, categories degraded and unproductive lands lisomelioratsiya, lines of action.